THE BENEFITS OF MASSAGING ON SUBJECTIVE PHYSIOLOGICAL COMPLAINTS IN THE SECOND SEMESTER STUDENTS OF IKOR FIK UNIVERSITAS NEGERI MANADO - Fentje Langitan (OLYMPUS: Jurnal Pendidikan Kesehatan dan Rekreasi, 2020)
From fact of field observation both physical education teachers and coaches do not understand the importance of the implementation of massage for warming up and cooling down dynamically, in one activity or sport and exercise activities at that time. More than that, athletes who doing massage at rest to go on set or the next round there massage very useful role for the recovery and physical condition, injury prevention. This formulation of the research problem is whether the benefits of massaging on the lack of physiological complaint in the second semester students of IKOR FIK. The method in this study is a quasi experimental design with one group pre text post text only design. Data analysis techniques used for the purpose of testing the hypothesis in this study in the use statistic Wilcoxon signed rank text. Based on data collection and data processing, it can be concluded that massaging can be benefits to the decline of subjective physiological complaints in the second semester students of IKOR FIK UniversitasNegeri Manado.